WISP: A pattern‐based approach to the interchange of scientific workflow specifications. (12th May 2016) - Bastos, Bruno F.; Braga, Regina Maria M.; Gomes, Antonio Tadeu A.
Summary: Scientific workflows are used for dealing with complex problems in different e‐science domains. These workflows are modeled and executed using Scientific Workflow Management Systems (SWfMSs). Generally, SWfMSs provide their own Workflow Specification Language, and this is a challenge considering the possibility of interchanging workflow specifications between different SWfMSs. In this paper, we propose the use of workflow patterns combined with software architecture concepts to capture the key semantics expressed in scientific workflows specified in different Workflow Specification Languages. These concepts are materialized in a novel specification interchange language (and associated tooling) called Workflow Interchange in Science with Patterns (WISP), which is the main contribution of our work. We have evaluated WISP based on real world specifications; in this paper, we present the results of such evaluation (including an assessment of the quality of the research material available), which has eventually led us to reformulate our initial proposal with more stringent assumptions on the input and output specifications. Copyright © 2016 John Wiley & Sons, Ltd.